“WAYS AND OPPORTUNITIES FOR DEVELOPING DOMESTIC TOURISM IN UZBEKISTAN” (Лучшие интеллектуальные исследования, 2025)
This article analyzes the current state and future prospects of domestic tourism development in Uzbekistan. With a focus on internal travel among the country’s population, it discusses the importance of domestic tourism in promoting national economic growth, creating local employment opportunities, and fostering cultural identity. The article reviews recent government initiatives aimed at supporting internal tourism, such as infrastructure development programs, public awareness campaigns, and seasonal travel discounts. It also outlines key challenges including high travel costs, limited digital integration, and insufficient facilities in rural tourist areas. Finally, the article proposes practical solutions and opportunities—such as improving transportation networks, enhancing service quality, and leveraging digital technologies—to stimulate sustainable domestic tourism and increase local participation in the exploration of Uzbekistan’s rich historical and natural heritage.